International Meeting of Young Researchers in Structural Geology and Tectonics (YORSGET-08): introduction - Gutiérrez-Medina, M.; Poblet, J.; Pedreira, D.; López-Fernández, C. (TRABAJOS DE GEOLOGÍA, 2009)
This volume of the journal Trabajos de Geología includes a selection of reviewed versions of extended abstracts presented at the “International Meeting of Young Researchers in Structural Geology and Tectonics (YORSGET-08)” held at Oviedo (Spain) from June 28th to July 3rd, 2008.